Development of English Teaching Module for Electrical Engineering Study Program - Atiqah Nurul Asri; Aly Imron; Satrio Binusa Suryadi (SAGA: Journal of English Language Teaching and Applied Linguistics, 2022)
The proper teaching materials determine successful teaching-learning. Teaching materials are required to adapt to the current situation of the institution, curriculum, and learners. The new curriculum adopted by the Electrical Engineering Study Program required the updated version since English courses had been replaced by the first and last semester of both the D3 and D4 programs. Developing the new teaching materials for the study program aimed to provide relevant issues and teaching strategies that could boost students' motivation in the classroom. Thus, the developed teaching materials were to propose the teaching and learning that fit the learner's needs. The research objective was to develop new teaching modules for the Electrical Engineering Study Program that were much more interactive, effective, and efficient for the learners to study English within the Electrical Engineering context. This research applied Research and Development (R&D) model adopted from Borg and Gall comprising six stages, namely: (1) needs analysis, (2) designing the product, (3) proposing the product, (4) evaluating the product, (5) testing and (6) disseminating the product. As a result, the new teaching module was redesigned to provide English teaching and learning effectively and efficiently that could be easily understood and helpful for the student to achieve the learning outcomes as expected.